Daclatasvir and Sofosbuvir Therapy Enhance Monocyte Phenotypic Changes in Naive Chronic Hepatitis C Patients: A Prospective Cohort Study - Hanan M. Fayed; Ali A. Ghweil; Mona M. AbdelMeguid (Interdisciplinary Perspectives on Infectious Diseases)
Background. Liver inflammation influences monocyte function, recruitment, and consequently inflammatory and fibrogenic responses. We aimed to investigate changes in the circulating monocyte phenotypes in response to Daclatasvir-Sofosbuvir (SOF/DCV) therapy in chronic hepatitis C (CHC) and relate findings to the viral kinetics and the fibrosis score. Methods. A longitudinal study involving 100 treatment-naïve patients and 30 healthy controls, tested for liver function, fibrosis scores (AST to platelet ratio index, FIB-4), and blood monocyte subsets based on CD14/CD16 expression by flow cytometer. Results. CHC patients had significantly lower albumin, higher ALT, AST, alkaline phosphatase, and increased fibrosis scores [Fib-4 (1.85±0.98) and AST to platelet ratio index (APRI) (0.6±0.35)], higher monocyte and eosinophil counts and lowered neutrophil to monocyte ratio (NMR), and lymphocyte to monocyte ratio (LMR) compared to week 12 and control. CHC patients had significantly increased median [classical (52.2% versus 25.8%, P=0.004) and inflammatory CD16+ monocytes (23.1% versus 13.58%, P=0.035)]. Therapy results in achievement of sustained virological response in 92% of cases, liver function improvement, and normalization of the inflammatory monocytes subsets. Monocyte counts showed positive correlation with viral load, calculated fibrosis scores (APRI and FIB-4 score), AST, ALT, ANC, and inverse correlations with serum albumin, leukocyte, eosinophil, NMR, and LMR. Multivariate regression found eosinophil count as predictors of CD16+ monocyte count in CHC patients. Conclusion. CHC infection promotes a proinflammatory and profibrotic monocytes profile. SOF/DCV therapy efficiently decreases viral load, reduces fibrosis potentials, attenuates monocyte activation, normalizes monocytes phenotypic abnormalities, and modulates monocyte subsets recruitment and differentiation later in the liver.